1999
DOI: 10.1677/joe.0.1630139
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the progestin receptors in the human TE85 and murine MC3T3-E1 osteoblast-like cell lines

Abstract: Progestins are believed to exert positive effects on bone density through receptors located in osteoblasts. In the present studies, the binding characteristics and regulation of the progestin receptors in two osteoblast-like cell lines were compared with those in human breast lines. Human TE85 and murine MC3T3-E1 osteoblast-like cells contain a single, high-affinity progestin binding site whose affinity and concentration are lower than in human breast cells. The osteoblastic progestin binding sites showed the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 45 publications
(37 reference statements)
0
3
0
Order By: Relevance
“…Baylink (Loma Linda University, Loma Linda, CA, USA). These cells exhibit typical osteoblastic characteristics, (12) possess ERs (13) and have been used in a number of previous studies (8–10) …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Baylink (Loma Linda University, Loma Linda, CA, USA). These cells exhibit typical osteoblastic characteristics, (12) possess ERs (13) and have been used in a number of previous studies (8–10) …”
Section: Methodsmentioning
confidence: 99%
“…The experiments reported here were designed to establish whether human osteoblastic cells (HOBs) show similar responses to strain and estrogen as those observed in rat cells, and, thus, whether the mechanisms that these responses suggest are similar in these two species. To do this, we have used monolayer cultures of first‐passage primary HOBs (fHOBs) derived from female human bone salvaged from surgical procedures and the human osteosarcoma‐derived TE85 osteoblastic cell line (8–10) . We investigated the proliferative responses of these cells to a single, short period of cyclic mechanical strain and/or 17β‐estradiol in the presence and absence of the ER modulators ICI 182,780 and tamoxifen; monoclonal neutralizing antibody (MNAb) to IGF‐I and IGF‐II; and αIR‐3, a well‐characterized blocking antibody to the IGF‐I receptor.…”
Section: Introductionmentioning
confidence: 99%
“…[29][30][31] They have been widely used as experimental models for investigating osteoblast functions. [32][33][34][35][36][37][38] Optical images acquired at 6 h after initial seeding (Fig. 4) showed that TE85 cells attached to and spread over all surfaces examined.…”
Section: Resultsmentioning
confidence: 99%